2008
DOI: 10.1002/ar.20683
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of the Tight Junction Proteins, Claudin‐1, Claudin‐4, Occludin, ZO‐1, and PAR3, in the Ameloblasts of Rat Upper Incisors

Abstract: Tight junctions (TJs) create a paracellular permeability barrier to restrict the passage of ions, small solutes, and water. Ameloblasts are enamel-forming cells that sequentially differentiate into preameloblasts, secretory, transition, and ruffle-ended and smooth-ended maturation ameloblasts (RAs and SAs). TJs are located at the proximal and distal ends of ameloblasts. TJs at the distal ends of secretory ameloblasts and RAs are welldeveloped zonula occludens, but other TJs are moderately developed but incompl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
4
28
1
Order By: Relevance
“…These are a prerequisite for vectorial electrolyte secretion by restricting free transepithelial ion movements while permitting passage of certain ions between the cells (Hou, ; Melvin, Yule, Shuttleworth, & Begenisich, ; Steward, Ishiguro, & Case, ). The data are also in accordance with previous studies (Amasheh et al., ; Colegio, Van Itallie, McCrea, Rahner, & Anderson, ; Lal‐Nag & Morin, ) showing the expression of Cldn1, Cldn4, and Cldn8 in maturation‐stage ameloblasts (Hata, Kawamoto, Kawai, & Yamamoto, ; Inai, Sengoku, Hirose, Iida, & Shibata, ). As previous studies show, ion transporters necessary for intracellular and extracellular pH regulation such as Slc9a1/Nhe1, Slc4a2/Ae2, Slc4a4/Nbce1, Slc26a4/pendrin, and CFTR (Bronckers et al., ; Jalali et al., ; Lacruz et al., ) and the cytoplasmic Car2 isoform of carbonic anhydrases (Lacruz, Smith, Moffatt, et al., ; Reibring et al., ) are expressed by ameloblasts.…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By supporting
confidence: 92%
“…These are a prerequisite for vectorial electrolyte secretion by restricting free transepithelial ion movements while permitting passage of certain ions between the cells (Hou, ; Melvin, Yule, Shuttleworth, & Begenisich, ; Steward, Ishiguro, & Case, ). The data are also in accordance with previous studies (Amasheh et al., ; Colegio, Van Itallie, McCrea, Rahner, & Anderson, ; Lal‐Nag & Morin, ) showing the expression of Cldn1, Cldn4, and Cldn8 in maturation‐stage ameloblasts (Hata, Kawamoto, Kawai, & Yamamoto, ; Inai, Sengoku, Hirose, Iida, & Shibata, ). As previous studies show, ion transporters necessary for intracellular and extracellular pH regulation such as Slc9a1/Nhe1, Slc4a2/Ae2, Slc4a4/Nbce1, Slc26a4/pendrin, and CFTR (Bronckers et al., ; Jalali et al., ; Lacruz et al., ) and the cytoplasmic Car2 isoform of carbonic anhydrases (Lacruz, Smith, Moffatt, et al., ; Reibring et al., ) are expressed by ameloblasts.…”
Section: The Hat‐7 Cell Model To Functionally Study Ph Regulation By supporting
confidence: 92%
“…However, in incisors, pre-ameloblasts expressed ZO-1 at their basal end and little to no ZO-1 at their apical end. Once the ameloblasts reached the secretory stage, strong ZO-1 expression was observed at both the apical and basal ends (Unda et al, 2003;Inai et al, 2008). ZO-2, in contrast, was observed along lateral surfaces of pre-ameloblasts and across ameloblast cell membranes.…”
Section: Tight Junctions and Enamel Developmentmentioning
confidence: 99%
“…Claudin-1 (Joao and Arana-Chavez, 2004;Bello et al, 2007;Inai et al, 2008;Hata et al, 2010;Nishikawa and Abe, 2010), claudin-2 (Ohazama and Sharpe, 2007), claudin-4 (Inai et al, 2008), claudin-7 (Bello et al, 2007), and claudins -6, -8, -9, and -10 (Hata et al, 2010) were all shown to be expressed in ameloblasts. The most convincing data were generated from rat incisors and demonstrated that both claudin-1 (Nishikawa and Abe, 2010) and claudins-1 and -4 (Inai et al, 2008) were expressed in maturation-stage ameloblasts. Both studies showed that apical claudin-1 was removed from smooth-ended ameloblasts and was returned when the ameloblasts once again became ruffle-ended.…”
Section: Tight Junctions and Enamel Developmentmentioning
confidence: 99%
“…3B). It has been demonstrated that polarized ameloblasts have specific characteristics including a columnar cell shape and the localization of molecules including Par3, ZO-1 and F-actin at the apical edge 12. Immunohistochemical analyses further showed that this localization of Par3, ZO-1 and F-actin was disrupted in the sh Dpysl4 molar epithelium as compared with control molars (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…It has been reported that the formation of epithelial polarity is regulated by several signaling mechanisms including Phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ) kinase, Glycogen synthase kinase 3 beta (GSK3β), Partitioning-defective protein (PAR) complex and the Ras homolog gene family (Rho) of proteins through the rearrangement of the actin cytoskeleton and microtubules 9. Functional ameloblasts also have specific characteristics, including a columnar cell shape and the localization of molecules such as Par3 , zonula occludens (ZO) and filamentous actin (F-actin) at their apical edge 12. These cells synthesize and secrete enamel-specific proteins from their apical ends through the transportation of secretory vesicles along microtubules 13, 14.…”
Section: Introductionmentioning
confidence: 99%